Pengembangan Aplikasi Sistem Pengelolaan Data Penelitian di Lembaga Penelitian Universitas Negeri Makassar - Fathahillah; Abdul Muis Mappalotteng (Politeknosains, 2017)
The fact still difficult obtaining accurate data about the history of research lecturers UNM, the titles of studies that have been done, that finance institution, funding year, the amount of funding is often confusing. Moreover, if the data was needed example for stuffing the study program accreditation forms in which the lecturer is located, is still very difficult to obtain. This study aims to develop information systems for administrating data at research institutions in the State University of Makassar. This study uses a model type of R & D (Research and Development), the method of the System Development Life Cycle (SDLC). Research results generated in the form of a software built using web programming server to establish data management systems for research studies especially those of non-tax revenues in the Research Institute of the State University of Makassar.